Quantifying carbon and biomass in planted forests – a remote sensing perspective - Mat Daud, Mohd Muhaizi; Ismail, Mohd Hasmadi; Mohd Sood, Alias; Kamarudin, Norizah (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Planted forests are important sources of forest products such as roundwood, fuelwood and fibre. Planted forests also play a role in carbon emission and biomass storage and have implications on climate change mitigation. Carbon emissions and biomass of planted forests are uncertain. As such information on planted forest biomass storage and carbon stock is needed. Remote sensing, an important technology and tool, can provide spatial-temporal data on planted forest carbon and biomass studies which include identifying, monitoring and mapping of planted forest areas. This paper reviews the use of remotely sensed data in quantifying carbon and biomass in planted forests.